Repeated-sprint performance, locomotor profile and muscle oxygen uptake recovery: Effect of training background - Ufland, P.; Ahmaidi, S.; Buchheit, M. (International Journal of Sports Medicine, 2013)
The aim of the present study was to examine the respective importance of locomotor profile and muscle oxygen uptake (mV.O2) recovery on repeated-sprint ability (RSA) and overall repeated-sprint performance. 11 sprint- (STR) and 10 middle-distance-trained (MDTR) athletes (20.8±4.0 yr) performed an incremental test and a 40-to-50-m sprint to estimate their maximal aerobic (MAS) and sprinting (MSS) speeds. They also performed 6×30-m sprints, departing every 30 s, where mean (RSmean) sprint time was calculated. Muscle oxygenation (Near-infrared spectroscopy, NIRS, [Hbdiff]) was measured for ~ 4 min post test. The mean response time of [Hbdiff]-mV.O2 recovery (monoexponential curve fitting, MRT[Hbdiff]-mV.O2) was calculated. Compared with MDTR, STR presented faster MSS (+11.4±6.7%, with 99% chances to observe a substantially greater value) and RSmean (-3.7±5.4%, 78%), but slower MAS (-15.8±8.0%, 100%) and MRT[Hbdiff]-mV.O2 (+46.2±31.7%, 96%). RSmean was largely correlated with MSS [r=-0.83 (90%CL, -0.92;-0.67)], but neither with MAS [r=-0.12 (-0.47;0.25)] nor MRT[Hbdiff]-mV .O 2 [r=-0.27(-0.58;0.11)]. RSmean adjusted for MSS (which indirectly reflects RSA) was largely correlated with both MAS [r=0.51(0.18;0.74)] and MRT[Hbdiff]-mV.O2 [r=0.53(0.20;0.75)]. While a fast mV.O2 recovery is associated with an improved RSA, MSS remains of primary importance for overall repeated-sprint performance (i.e., RSmean).